2022
DOI: 10.3389/fnagi.2021.740491
|View full text |Cite
|
Sign up to set email alerts
|

Aquaporin-4 Polymorphisms Are Associated With Cognitive Performance in Parkinson’s Disease

Abstract: ObjectiveAquaporin-4 (AQP4) facilitates a sleep-enhanced interstitial brain waste clearance system. This study was conducted to determine the clinical implication of AQP4 polymorphisms in Parkinson’s disease (PD).MethodsThree-hundred and eighty-two patients with PD and 180 healthy controls with a mean follow-up time of 66.1 months from the Parkinson’s Progression Marker Initiative study were analyzed. We examined whether AQP4 SNPs were associated with an altered rate of motor or cognitive decline using linear … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 59 publications
1
28
0
Order By: Relevance
“…Conversely, alpha-synuclein has been shown to cause aggressive neuroinflammatory insults and AQP4 deficiency which perpetuates glymphatic impairment, causing dopaminergic degeneration in the SN as well as in other brain regions. Although a recent genetic study has shown associations between different AQP4 polymorphisms and varying rate of cognitive decline in PD [ 104 ], further work is vital to determine if a strong link exists between glymphatic dysfunction and the pathogenesis of the human disease.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, alpha-synuclein has been shown to cause aggressive neuroinflammatory insults and AQP4 deficiency which perpetuates glymphatic impairment, causing dopaminergic degeneration in the SN as well as in other brain regions. Although a recent genetic study has shown associations between different AQP4 polymorphisms and varying rate of cognitive decline in PD [ 104 ], further work is vital to determine if a strong link exists between glymphatic dysfunction and the pathogenesis of the human disease.…”
Section: Discussionmentioning
confidence: 99%
“…A study by Rainey-Smith et al (2018) utilized a self-reported “overall” sleep quality assessment and demonstrated that several AQP4 single nucleotide polymorphisms were associated with poorer sleep ( Rainey-Smith et al, 2018 ). Another recent study on Parkinson’s disease demonstrated that specific mutations in AQP4 were likely the cause of sleep disturbance and may act as a prognostic marker for cognitive decline ( Fang et al, 2022 ). Conversely, some studies have found that sleep disturbance results in AQP4 mislocalization; one such study found that mice who were sleep deprived showed AQP4 mislocalization away from astrocyte end-feet ( Liu et al, 2017 ).…”
Section: Glymphatic Systemmentioning
confidence: 99%
“…Regarding PD patients, Fang and collaborators have recently conducted a study to determine the clinical implication of AQP4 polymorphisms in PD [ 120 ]. They investigated whether AQP4 SNPs were associated with Aβ burden as measured by 18F Florbetapir standard uptake values and examined if AQP4 SNPs moderated the association between REM sleep behavior disorder (RBD) and CSF biomarkers [ 120 ]. They conclude that genetic variations of AQP4 and subsequent alterations of glymphatic efficacy might contribute to an altered rate of cognitive decline in PD [ 120 ].…”
Section: Aqp4 Expression and Polymorphisms In Ad And Pdmentioning
confidence: 99%
“…They investigated whether AQP4 SNPs were associated with Aβ burden as measured by 18F Florbetapir standard uptake values and examined if AQP4 SNPs moderated the association between REM sleep behavior disorder (RBD) and CSF biomarkers [ 120 ]. They conclude that genetic variations of AQP4 and subsequent alterations of glymphatic efficacy might contribute to an altered rate of cognitive decline in PD [ 120 ]. Furthermore, AQP4 rs162009 can be considered a novel genetic prognostic marker of glymphatic function and cognitive decline in PD [ 120 ].…”
Section: Aqp4 Expression and Polymorphisms In Ad And Pdmentioning
confidence: 99%
See 1 more Smart Citation